ANALYSIS OF QUALITY CONTROL OF TAPIOCA FLOUR PRODUCTS AT PT GUNUNG SUGIH - Iis Melinda; Ayi Ahadiat; Aripin Ahmad (Asosiasi Dosen Muda Indonesia, 2023)
PT Gunung Sugih is one of the industry players that produces tapioca flour in the form of 50 kg. Researchers conducted research on tapioca flour production in the input, process and output sections. The production process at PT Gunung Sugih has problems with raw materials, humans, machines, methods and the environment, causing damage to the product. The purpose of this study was to identify whether the level of damage that occurs in PT Gunung Sugih tapioca flour products is still within tolerance limits or not and to identify the factors that cause the most dominant damage. The method used in this study is the Statistical Process Control (SPC) method, with Check Sheet analysis tools, histograms, control charts and causal diagrams so that product damage that occurs can be indicated. The data sources used in this study are primary data and secondary data from PT Gunung Sugih in April 2023. Based on the existing data, statistical process control (SPC) analysis has been carried out, it is known that the damage that occurred in PT Gunung Sugih's tapioca flour production still within tolerance limits, and it is known that the main factors of product damage come from raw materials, people, machines and methods. The most dominant damage is damage to the water content that comes from the human factor, tapioca flour agglomerates from the machine and human factors, while the color damage is from the raw material and human factors, thus it is hoped that PT Gunung Sugih will improve operator supervision on raw materials, production processes and production results, work instructions can be given in writing and explained verbally at the beginning of each production and the end of work, hold regular and periodic meetings with employees, carry out periodic machine maintenance and provide safety equipment and silencers on the machine. this is to maintain product quality to remain good.